Characterization of nanoplastics and small-sized microplastics in sewage treatment - Shaima Iskandarani; Sarvajith Manjunath; Rosa Busquets; Lorenzo Raeli; Pascal E. Saikaly; Luiza C. Campos (Scientific Reports, 2025)
Abstract The presence of nanoplastics (NPs) in sewage treatment plants (STPs) remains a critical yet underexplored environmental issue. Here, we present a novel investigation into the occurrence, recovery, and characterization of nanoplastics and small-size microplastics (50–2500 nm) in raw and treated sewage effluent from a full-scale STP (treating 4000 m 3 /day) operating with activated sludge. To our knowledge, this research includes the first confirmed assessment of nanoplastics in such a system and applies nano-flow cytometry to wastewater analysis for the first time globally. It is also the first study addressing micro- and nanoplastics in wastewater in Saudi Arabia, advancing plastic particle analysis in complex matrices. Particles in the 50– < 100 nm range accounted for 44% of total particles detected in STP effluents. Overall, plastic particles accounted for 16% (± 10%) of total particles within 50-2500 nm in raw sewage, increasing to 41% (± 13%) in treated effluent. This increase highlights the inefficiency of conventional treatment in fully removing plastic particles and suggests preferential removal based on size or density. The composition of a representative selection of particles was characterized by micro-Raman spectroscopy and Scanning Electron Microscopy with Energy-Dispersive X-ray. Identified polymers included polystyrene, polyvinyl chloride, polyethylene, polytetrafluoroethylene, polyamide, and polypropylene. These findings provide important insights into treated sewage composition, particularly for reuse in arid regions.